Policy for building safety accident prevention system using beacon-based technology: Focused on school safety policy cases - Lee, Gi Hyun; Chung, Myoung Sug; Lee, Joo Yeoun (Proceedings - 2021 IEEE International Conference on Big Data and Smart Computing, BigComp 2021, 2021)
This paper aims to discover applicable technologies to reduce the number of safety accidents that may occur in the surroundings and to strengthen safety systems using technologies related to the 4th Industrial Revolution, and to study the possibility and efficiency of introducing the discovered technologies.. Focusing on school safety policy cases, I would like to propose an example of a safety system applying new technology. Overseas countries are already demanding technical support to keep students safe while going to and from school. In Korea, technologies to make the way to and from school more safely have been introduced, but the rate of increase in cases introduced abroad is relatively high. Therefore, with the goal of safe school life, we propose a safety system construction process by deriving technologies that can operate highly efficient systems.
Keywords: Building safety; Industrial revolutions; Prevention systems; Rate of increase; Safety accidents; Safety policies; System construction; Technical support; 4IR(4th Industrial Revolution); Beacon; Safety Accidents; School Safety